Assessment of Carotid Intima-media Thickness in COVID-19 Survivors - Yasemin Doğan; Ayşe Turunç Özdemir (International Journal of the Cardiovascular Academy, 2023)

(untitled)
Background and Aim:Coronavirus disease-2019 (COVID-19) infection is associated with cardiovascular diseases in the acute and chronic stages. One of the most common causes of death worldwide is atherosclerosis. Carotid intima media thickness is a method used in the early diagnosis and follow-up of atherosclerosis. This study describes endothelial dysfunction and the risk for pre-atherosclerosis using carotid intima-media thickness (CIMT) measurements in patients with a history of COVID-19 infection.Materials and Methods:This was a prospective case-control study of 121 patients with 121 COVID-19 infections and 40 healthy controls. Groups were compared according to demographic characteristics, body mass index (BMI), and carotid intima-media thickness. Data obtained were analyzed using SPSS version 22.0.Results:There was no statistically significant difference between the groups in terms of age, gender, BMI, and blood pressure values. The CIMT value of the group with COVID-19 infection was significantly higher than the control group (P = 0.003).Conclusion:The findings of this study show that CIMT, which is an indicator of early atherosclerosis, was increased in patients with COVID-19.